SOSIALISASI TENTANG KEJAHATAN CYBERCRIME DAN PENTINGNYA KEAMANAN DATA PRIBADI - Muhammad Rufli; Sasikirana Fawwaz Fikah; Afrina; Andi Hepy Susanti; Hanafi; Taslimahuddin (J-COSCIS : Journal of Computer Science Community Service, 2025)
Community Service Program: Socialization on Cybercrime and the Importance of Personal Data Security for the Residents of Bengkong Kolam Mas, Bengkong Sadai Village, Bengkong District, Batam City By Group 4 of the Community Service Program (KPM), Faculty of Science and Technology, Ibnu Sina University, Academic Year 2024/2025. The aim of this program is to raise awareness and understanding among the community about the threats of cybercrime in the digital era. The activity includes an initial survey to assess the community's level of knowledge, the delivery of theoretical material on various types of cybercrime, prevention practices, and an evaluation through pre-tests and post-tests. Participants were provided with insights on the importance of safeguarding personal data, recognizing different forms of digital fraud, and security measures when using devices and internet services. The results of the program indicate an increase in participants' understanding of cybercrime after attending the socialization session. Participants have become more aware of the importance of digital security and recognizing cyber threats in their daily lives. Positive feedback suggests that this program is effective as a model for digital literacy education and efforts to prevent cybercrime in the Batam City community.